The Effect of Xinmailong Infusion on Sepsis-Induced Myocardial Dysfunction: a Pragmatic Randomized Controlled Trial. Issue 1 (January 2021) - He, Jianzhuo; Zhao, Xujie; Lin, Xinfeng; Yang, Zhixu; Ma, Mingyuan; Ma, Li; Liang, Qun; Li, Lan; Ye, Yong; Wen, Zehuai; Zhang, Zhanlin; Zhang, Minzhou; et al.
Abstract : ABSTRACT: Sepsis-induced myocardial dysfunction (SIMD) contributes significantly to cardiovascular dysfunction during septic shock. We aimed to evaluate the potential role of Xinmailong injection (XMLI), a polypeptide medicine extracted from Periplaneta americana, in reversing the progression of myocardial damage to SIMD in sepsis patients. This was a multicenter, randomized, double-blind, parallel-group trial. We recruited all patients consecutively admitted to intensive care units (ICUs) who were aged 18 to 85 years old and met the sepsis 3.0 criteria. The primary outcome measure was the incidence of sepsis-induced myocardial dysfunction while in the ICU. Of the 192 patients, 96 were assigned to the treatment group, and 96 to the control group. Subsequently, 41 patients [41/96 (42.7%)] in the XMLI group and 61 patients in the placebo group [61/96 (63.5%)] were confirmed to have diastolic dysfunction on the fifth day (D5). The incidence of diastolic SIMD was significantly different between the two groups ( P = 0.004). There were 36 deaths in the two groups during the 28-day follow-up, with a general mortality rate of 18.8% (36/192). The 28-day mortality rates were not significantly different between the groups ( P = 0.45). However, the brain natriuretic peptide (BNP) plasma concentration trends on D0, D2, and D5 significantly differed between the two groups ( P = 0.049). In septic patients, XMLI decreased the occurrence rate of diastolic SIMD more effectively than the placebo. The improvement in serum BNP concentration was also greater in the XMLI group. XMLI may, therefore, effectively and safely improve cardiac function in patients with sepsis. Abstract : Supplemental Digital Content is available in the text